2006
DOI: 10.1007/s11033-006-0009-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA Bending in the Replication Zone of the C3 DNA Puff Amplicon of Rhynchosciara americana (Diptera: Sciaridae)

Abstract: Intrinsic bent DNA sites were identified in the 4289 bp segment encompassing the replication zone which directs DNA amplification and transcription of the C3-22 gene of Rhynchosciara americana. Restriction fragments showed reduced electrophoretic mobility in polyacrylamide gels. The 2D modeling of the 3D DNA path and the ENDS ratio values obtained from the dinucleotide wedge model of Trifonov revealed the presence of four major bent sites, positioned at nucleotides -6753, -5433, -5133 and -4757. Sequence analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…The generated recombinant pBendBlue plasmids are then introduced into host bacteria by means of DNA transformation and selected by a direct assay. The plasmid DNA is isolated by minipreparation and digested in independent reactions with suitable restriction enzymes, which recognize the duplicated pBendBlue polylinker, yielding a set of circularly permutated DNA fragments of identical size, but with a permutated bent position (Fiorini et al, 2006a;Gimenes et al, 2008b;Gimenes et al, 2009;Sperbeck & Wistow, 1998 Fig. 4.…”
Section: Circular Permutation Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…The generated recombinant pBendBlue plasmids are then introduced into host bacteria by means of DNA transformation and selected by a direct assay. The plasmid DNA is isolated by minipreparation and digested in independent reactions with suitable restriction enzymes, which recognize the duplicated pBendBlue polylinker, yielding a set of circularly permutated DNA fragments of identical size, but with a permutated bent position (Fiorini et al, 2006a;Gimenes et al, 2008b;Gimenes et al, 2009;Sperbeck & Wistow, 1998 Fig. 4.…”
Section: Circular Permutation Assaymentioning
confidence: 99%
“…In the same work, the in silico analysis of the replication origin segments from X. fastidiosa Temecula, Bacillus subtilis and Escherichia coli showed that all of the replication sites, with some variability in their helical parameters, displayed curved segments. In eukaryotes cells, our work was associated with gene amplified domains in developmental systems (Fiorini et al, 2001;2006a;Gimenes et al, 2009) and induced gene amplified segments in mammalian culture cells (Balani et al, 2010). Using the developmental amplified models, we analyzed amplicons from the gene BhC4-1 from Bradysia hygida (Fiorini et al, 2001), an amplified segment of the C3-22 gene from Rhynchosciara americana and in the segment DAFC-66D from chromosome 3 of Drosophila melanogaster, which contains the amplification control element ACE3 and the replication origin ori-β (Gimenes et al, 2009).…”
Section: Possible Roles Of Intrinsically Bent Dna In Replicationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the intrinsic curvature of DNA plays an important role in cellular processes such as nucleosome compaction (8), recombination processes (9), fragile sites (10), tandem repeated sequences (11), replication origins (12,13), Scaffold/Matrix Attachment Regions (S/MARs) (14) and MARs associated with replication origins (13,15).…”
Section: Introductionmentioning
confidence: 99%